A GPU-based machine learning approach for detection of botnet attacks. Issue 123 (December 2022) - Motylinski, Michal; MacDermott, Áine; Iqbal, Farkhund; Shah, Babar
Abstract: Rapid development and adaptation of the Internet of Things (IoT) has created new problems for securing these interconnected devices and networks. There are hundreds of thousands of IoT devices with underlying security vulnerabilities, such as insufficient device authentication/authorisation making them vulnerable to malware infection. IoT botnets are designed to grow and compete with one another over unsecure devices and networks. Once infected, the device will monitor a Command-and-Control (C&C) server indicating the target of an attack via Distributed Denial of Service (DDoS) attack. These security issues, coupled with the continued growth of IoT, presents a much larger attack surface for attackers to exploit in their attempts to disrupt or gain unauthorized access to networks, systems, and data. Large datasets available online provide good benchmarks for the development of accurate solutions for botnet detection, however model training is often a time-consuming process. Interestingly, significant advancement of GPU technology allows shortening the time required to train such large and complex models. This paper presents a methodology for the pre-processing of the IoT-Bot dataset and classification of various attack types included. We include descriptions of pre-processing actions conducted to prepare data for training and a comparison of results achieved with GPU accelerated versions of Random Forest, k-Nearest Neighbour, Support Vector Machine (SVM) and Logistic Regression classifiers from the cuML library. Using our methodology, the best-trained models achieved at least 0.99 scores for accuracy, precision, recall and f1-score. Moreover, the application of feature selection and training models on GPU significantly reduced the training and estimation times.